The Impact of Authentic Materials and Tasks on Students’ Communicative Competence at a Colombian Language School (2017)
This article reports on a study carried out in a foreign language school at a Colombian public university. Its main purpose was to analyze the extent to which the use of authentic materials and tasks contributes to the enhancement of the communicative competence on an A2 level English course. A mixed study composed of a quasi-experimental and a descriptive-qualitative research design was implemented by means of a pre-test, a post-test, observations, semi-structured interviews, surveys, and diaries. The findings showed that the use of authentic materials and tasks, within the framework of a pedagogical project, had an impact on students’ communicative competence progress and on the teaching practices of the experimental group teacher.